RESPONSE OF SOME TYPES OF MICROORGANISM-LOCALIZED (MOL) TO PAKCHONG GRASS GROWTH (Pennisetum Purpureum Cv. Thailand) - Aswin, Muhammad; Meriksa Sembiring (Journal of Innovation Research and Knowledge, 2024)
Response of local micro-organisms (MOL) to the growth of pakchong grass (Pennisetum purpureum Cv. Thailand). The purpose of this study was to determine the response of several types of Local Micro-Organisms (MOL) to the growth and productivity of Pakchong grass (Pennisetum purpureum Cv. Thailand). This study used a non-factorial Group Randomized Design (RAK) with 4 treatments and 6 repeats, with treatments being: Po (without MOL), P1 (MOL Nature Gene), P2 (D' Boostefer), and P3 (Pamorganic MAS). How to apply MOL to plants is to use 50 ml of liquid organic fertilizer with 4.95 liters of water and then flush each treatment plot. Application is carried out one week after planting, then repeated once every 2 weeks until the plant is 6 weeks old. The parameters observed were plant height growth, stem diameter, number of leaves, and production of fresh and dried grass. The results showed that the use of several types of MOL on Pakchong grass had a real effect (p < 0.05) on the growth and productivity of Pakchong grass compared to P0 (control). The best results were P2 >P3 > P1, while the lowest growth and production were found at P0 (Without MOL) which differed markedly from the use of MOL in Pakchong grass.